Pengaruh Auditor Cient Tenure, Reputasi Audit dan Ukuran Perusahaan Terhadap Audit Going Concern pada Perusahaan Manufaktur di Bursa Efek Indonesia - Clara P. Georgina Hutabarat; Orina Siregar Sudjiman (Jurnal Pengetahuan dan Pendidikan, 2024)
This study aims to anayze the effect of auditor cient tenure, audit reputation and company size on going concern audits in food and beverage sub-sector manufacturing companies isted on the Indonesia Stock Exchange in 2019-2021. This research method uses quantitative methods by performing data anaysis techniques used in this study are descriptive statistics, muticoinearity test, overa fit mode test, mode feasibiity test, coefficient of determination, cassification matrix test and ogistic regression significance test. Sampe data obtained from as many as 27 companies with a tota sampe of 81. The resuts of this study indicate that hat (1) Auditor Cient Tenure has no significant effect on Going Concern Audit (2) Audit reputation does not have a positive effect on Going Concern Audit, and (3) Company Size has no effect on Going Concern Audit.